Insights into Hospitalized Children with Urinary Tract Infections: Epidemiology and Antimicrobial Resistance Patterns in Israel—A Single Center Study - Hussein Zaitoon; Jenny Garkaby; Basheer Nassrallah; Livnat Sharkansky; Morya Shnaider; Irina Chistyakov; Jacob Genizi; Keren Nathan (Children, 2024)
Background: The escalating resistance of uropathogens in pediatric febrile urinary tract infection (F-UTI) is a global concern. This study examined changing trends in F-UTI epidemiology and resistance patterns among Israeli pediatric inpatients over a decade. Methods: Demographic, clinical, and laboratory data for children between 3 months and 18 years old with febrile UTI from 2010 to 2021 were retrieved from electronic medical records. Results: A total of 761 cases of F-UTI were identified (702 females, mean age 43 months). Escherichia coli was the most common pathogen (85.9%), followed by Pseudomonas aeruginosa (3.5%) and Klebsiella pneumoniae (3.4%). Compared with the non-complicated UTI group, the complicated UTI group had significantly higher rates of Pseudomonas aeruginosa (5.3% vs. 1.0%, p = 0.002) and Klebsiella pneumoniae (4.6% vs. 1.6%, p = 0.03). Antibiotic resistance analysis revealed significant differences between the groups: resistance to cephalexin was higher in the complicated UTI group (19.3%) compared with the non-complicated UTI group (13.4%, p = 0.03). Notably, relatively low resistance rates were observed for ceftriaxone (4.4%) and gentamicin (6.0%). Over time, a significant decreasing trend in resistance to ampicillin was observed (slope = −0.0193, p = 0.011). No significant trends were found for trimethoprim–sulfamethoxazole, cephalexin, amoxicillin–clavulanic acid, ceftriaxone, and cefuroxime. Conclusions: Significant differences in pathogen distribution and resistance patterns between complicated UTI and non-complicated UTI groups highlight the need for continuous resistance monitoring and adherence to local guidelines. For the treatment of severe community F-UTI, ceftriaxone could be a reasonable option for first-onset F-UTI. Further studies are needed to implement antibiotic stewardship and optimize usage.